Immobilized bis-layered ionic liquids/peroxotungstates as an efficient catalyst for selective oxidation of alcohols in neat water. (17th November 2016) - Fan, Juan; Pu, Fan; Sun, Man; Liu, Zhong-Wen; Han, Xiao-Yan; Wei, Jun-Fa; Shi, Xian-Ying
Abstract : An environmentally benign and reusable immobilized ionic liquids/peroxotungstates catalyst has been developed for the selective oxidation of alcohols to the corresponding carbonyls with aqueous H2 O2 in neat water without any co-organic solvent. Abstract : An immobilized ionic liquids/peroxotungstates/SiO2 catalyst was prepared and characterized. The catalyst was proved to be very efficient for the selective oxidation of primary and secondary alcohols to their corresponding carbonyls with benign H2 O2 as an oxidant in neat water. A 1.0 mol% (based on tungstate) dose of the catalyst was found to be sufficient for the oxidation. The catalyst is easily recovered after reaction via simple filtration, and was reused at least six times without a noticeable loss of the activity. A notable feature of this novel protocol is avoiding any organic co-solvent.